THE DEVELOPMENT OF LEARNING MEDIA OF PANJAT PINANG BIO BOARD GAMES AT THE CLASS XI OF MA GUPPI SAMATA - Ainul Uyuni Taufiq; Asniati Jabbar; Zulkarnaim Zulkarnaim (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:This research aimed to: (1) develop learning media of Panjat Pinang Bio Board Games based on circulation system material for class XI of MA GUPPI Samata, (2) determine the level of validity, practicality, and effectiveness of Panjat Pinang Bio Board Games. The research method employed was Research and Development (R & D) with the 4-D development model, namely define, design, develop, and disseminate. The instruments used were validation sheets, educator and student questionnaires, and questions. The population was 24 students of class XI, and six students were selected as samples. The results indicated that the average validity level was 3.62 with valid category, while the average practicality level was 3.10 with practical category. The level of efficacy was 100% which fulfilled the completeness criteria with effective category. Therefore, Panjat Pinang Bio Board Games was considered practicable to employ since it matched the criteria of being valid, practical, and effective. Selecting appropriate learning media supports students' learning outcomes. Abstrak:Penelitian bertujuan (1) mengembangkan media pembelajaran Bio Board Gamess Panjat Pinang pada materi sistem sirkulasi kelas XI MA pesantren GUPPI Samata, (2) mengetahui tingkat kevalidan, kepraktisan, dan keefektifan media pembelajaran Bio Board Gamess Panjat Pinang pada materi sistem sirkulasi kelas XI MA pesantren GUPPI Samata. Metode penelitian yaitu research and development (R & D) dengan model pengembangan 4-D yaitu define, design, develop dan disseminate. Instrumen penelitian yang digunakan di antaranya lembar validasi, angket respon pendidik dan peserta didik, dan soal. Populasi dalam penelitian ini adalah siswa kelas XI dan terpilih 6 orang sebagai sampel. Hasil penelitian menunjukkan tingkat validitas 3,62 dengan kategori valid, tingkat kepraktisan rata-rata 3,10 dengan kategori praktis. Tingkat keefektifan mencapai 100% yang memenuhi nilai KKM dengan kategori efektif. Sehingga media pembelajaran Bio Board Gamess Panjat Pinang layak digunakan karena memenuhi kriteria valid, praktis dan efektif. Pemilihan media pembelajaran yang tepat mendukung hasil belajar siswa.